ANALISIS PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU SISWA DI SMPNEGERI 1 MAZINO - Melani Sarina Gohae (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This problem concerns the use of social media, where social media is a social interaction between individuals in sharing and exchanging information. Social media can contain various ideas, opinions, notions and content in virtual communities and is able to present and neutralize new ways of communicating with technology. which is completely different from traditional media. Students use social media at SMP Negeri 1 Mazino to share and exchange information through social media such as Whatsapp, Facebook, Tiktok, You Tube. Where Facebook is used to share information and exchange information, Tiktok is used as information material when watching a video, WhatsApp is used as an information notification, and YouTube is used to obtain information in every video that students watch. Students in using social media are always monitored and directed by teachers in using social media, so that students at SMP Negeri 1 Mazino have good behavior in using social media.